(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Cholinesterase inhibitors are the class of compounds which inhibit cholinesterase enzyme. These are used as drugs for symptomatic treatment of Alzheimer’s disease (AD). The present study, evaluate anti-cholinesterase property of an aqueous extract of Mentha longifolia leaves, which is an aromatic plant traditionally used for several medicinal properties. Ellman’s method was used to determine the acetylcholinesterase (AChE) enzyme inhibitory activity of an aqueous extracts of Mentha longifolia leaves which showed concentration dependent AChE inhibition with maximum inhibition of 62.82 ± 0.005% at 25μg/ml final concentrations with IC50 value of 8.004μg/mL. The kinetic study using Lineweaver-Burk plot of an aqueous extract of Mentha longifolia leaves showed mixed non-competitive mode of inhibition against AChE. The anti AChE enzyme activity exhibited by an aqueous extracts of Mentha longifolia leaves extracts might be used in future for symptomatic treatment of AD.